Bioremediation of Heavy Metals: A Substantive Potential for Clean Earth - Das, Jyotirmayee; Dangar , Tushar K; Panigrahy, Madhusmita (Journal of Sustainable Materials Processing and Management, 2022)
Modernindustrialand agriculture developments, anthropogenic activities effectedterrestrial and aquatic pollution of heavy metalsposing serious threatsto biotic (human/animal/plant) and environmental health, as well as, welfareofany nation.Phytoremediation of metal pollutedsiteshas attracted worldwide significancedue to its being less expensiveand environment-friendlyproperties. Robust information is availableon heavy metal remediation, phytoremediation and severalplants are recordedworldwidewhich hyper accruewide category ofheavy metals. This communication emphasizesvariousremediation methods,especially phytoremediationfor heavy metalsalong withits advantage compared to othertechniques. Phytoremediation techniqueis specifically applicable for reclamationofsites with low to moderatepollutionleveldue to its being energyefficientand aesthetically pleasant, alsoit can be co-practised with variousconventionalremedial processesas anultimateprocedurefor remediationprocess.